Insight into the limited electrochemical activity of NaVP2O7. Issue 80 (2nd September 2015) - Kee, Yongho; Dimov, Nikolay; Staikov, Aleksandar; Barpanda, Prabeer; Lu, Ying-Ching; Minami, Keita; Okada, Shigeto
<x xml:space="preserve">Abstract</x> Recently, LiVP2O7 has been investigated as a possible high-voltage substitute for Li2FeP2O7.